PENERAPAN MODEL PREDICTIVE CONTROL (MPC) PADA FLOW LINE SISTEM PRODUKSI MENGGUNAKAN ALJABAR MAX-PLUS - Fauzi, Imam; Adzkiya, Dieky (Department of Mathematics Education , University of Jember, 2022)
Model Predictive Control (MPC) is a controller design method is popularly used in the industrial world. This research will be presented at the MPC application of flow line production system modeled using max-plus linear systems. The main advantage of the MPC is its ability to provide certain constraints or limits on the control signal input and output. Flow line of production systems is a diagram illustrating the process sequence in the production system, ranging from the input, processing and output. Of flow line production system, be applicable MPC as time optimization control of the production process. Furthermore, the results of the input and output MPC construction of a flow line production system can be obtained by using matlab program